Rola klastrów w kształtowaniu struktury i jakości produktu turystycznego regionu - Rapacz, Andrzej (The Role of Clusters in the Structure and Quality Construction of the Region's Tourist Product, 2008)
The need for increasing the competitiveness of a tourist traffic reception area facilitates the implementation of clusters' theory. The hereby study attracts attention to the theoretical aspect of clusters' functioning, pointing to its usefulness in tourism. The crucial element of the study becomes the identification of advantages resulting from the tourist clusters construction and referring mainly to the problems of diversifying the structure of such clusters' offer, as well as creating quality in tourism. Theoretical remarks are illustrated by the examples of a few tourist clusters functioning in the world. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 106-117